The Inner Wall of The Tank Painted in Black is Good for Larval Rearing of Yellowfin Tuna Thunnus albacares - Hutapea, Jhon Harianto; Gunawan, Gunawan; Setiadi, Ananto; Slamet, Bedjo (Indonesian Aquaculture Society (MAI), 2019)
Institute for Mariculture Research and Fisheries Extension have been able to spawn yellowfin tuna in the floating nets cage (FNC) since 2015. However, the number of juveniles produced is still low due to the high mortality of larvae at first 10 days old and when metamorphosed into juveniles. The inner wall color of tank is suspected to affect the survival of early larvae stage. The purpose of the study is to get suitable inner wall color of the tank to increase growth and survival rate. Eggs harvested from FNC and stocked 20 eggs/L in 5 Fiberglass Reinforced Plastic tanks, volume of 6 m3. Treatments were: A. Gray, B. Blue, C. Yellow, D. Black, and E. White, 3 replication. Hatching rate of eggs at treatment (A) was 60.39%, blue (B) 76.64%, yellow (C) 61.74%, black (D) 71.08% and white (E) 69.19%. Daily observation of Yellowfin tuna larvae kept in blue, yellow and white inner wall tank are more patched in the corner near the surface of the tank. While the larvae in the gray and black inner wall tank were distribute evenly either in the surface layer and water column. The survival rate of juvenile in black inner wall tank is better than others color treatments, although statistically does not significantly different.